Designing a Digital Mini Stage Augmented Reality Catalog Application Using the Loading Package Model Feature: Perancangan Aplikasi Catalog Digital Mini Stage Augmented Reality Menggunakan Fitur Model Loading Package - Syahgita, Mico Hari; Dijaya, Rohman (Universitas Muhammadiyah Sidoarjo, 2023)
The street vendor business is one that is growing rapidly in this day and age. Some of these businesses are personal in nature, while others are not. The interest in this research stems from observations made with street vendors, where the service for ordering booths so far only uses photo media without the ability to explore in greater detail, where the service is not optimal if the manual method is still used, and thus it is necessary to develop new services to be able to display products in 3D and explore thoroughly. The author's goal in conducting this research is to develop applications so that partners can increase consumer traffic through digital catalogs using augmented reality (AR) technology and make it easier for buyers to interactively visualize booth models. The results of this study are augmented reality applications for interactive visualization of booth models. The booth is displayed in three dimensions using a 3D developer application. Users can explore booth models i teractively from all sides. This application is a portable digital catalog that provides a more intuitive user experience.